More Growth, Less Garbage - Kaza, Silpa; Shrikanth, Siddarth; Chaudhary, Sarur (World Bank, Washington, DC, 2021)
More growth, less garbage presents an updated picture of how waste generation can grow if the world continues along the current trajectory and how to consider changing that path toward lower waste levels. Waste generation is estimated to grow from 2.24 billion tons in 2020 to 3.88 billion tons in 2050. Historically there has been a correlation between waste generation and income per capita. This publication explores the possibility of decoupling waste generation, and thus consumption, from economic growth. Five case studies of waste reduction, in terms of residual waste and or total waste, are highlighted from cities and countries across the world. In each location, decisions to reduce or divert waste were driven by a different factor, such as lack of land, the need to be more resilient, or the need to reduce costs of the overall waste system. If waste reduction policies were adopted in more places around the world, one can envisage a world in 2050 with more growth and less garbage than today.